Os irmãos Roberto e a arquitetura moderna no Rio de Janeiro (1936-1954) - Pereira, Claudio Calovi (1993)
This dissertation intends to analyse the architectural work of the brothers Marcelo, Milton and Maurício Roberto done in Rio de Janeiro between 1936 and 1954. This period embraces one of the most important moments in the history of Brazilian architecture, being at the same time a research area where the absence of theoretical and critical investigations must be faced. This is one of the purposes of this work. The analysis is centered in the building and its processes of configuration, trying to unfold the theoretical and methodological contents of the project, wich arises from the comprehension and interpretation of the building as material reality. Some representative works of M.M.M. Roberto were selected and through its description and analysis some conclusions were formulated in relation to the originality of the contributions and the connections with the architectural context in Brazil at that time. The international references are mainly related to the work of Le Corbusier and the influence of French academic tradition. The results intend to prove the significance of the works of M.M.M. Roberto as a design experience in the context of Brazilian modern arcgitecture between 1930 and 1960.